TYPES OF WRITING ACTIVITIES IN TEACHING FOREIGN LANGUAGE - Elmuratova, Z. (SCIENCE and SOCIETY, 2020)
This article is devoted to one of the important teaching skills as writing. The author of the work deals with the issues of designing writing activities to the learners studying foreign languages. Writing activities promote to the better knowledge of the material in the learning process, and also let check and assess the students’ knowledge.
Keywords: writing; process; picture; task; discussion; teaching; idea; opportunity; sentence; teacher